2016
DOI: 10.12998/wjcc.v4.i8.213
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis by pancreatic duct stenting using a loop-tipped guidewire

Abstract: The results suggest that in patients who experience difficulties with biliary cannulation, the use of a loop-tipped guidewire for pancreatic duct stenting may assist with the prevention of post-ERCP pancreatitis, and thereby to a reduction of the risk of post-ERCP pancreatitis or hyperamylasemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In clinical practice, for patients at risk of post-ERCP pancreatitis, the MICHISUJI may be clinically useful, although confirmation in a clinical trial is needed. However, although the loop shape may help prevent duct penetration 10 11 , creation of the loop shape may make guidewire passage through stricture sites more challenging. This function should therefore also be evaluated in an experimental study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, for patients at risk of post-ERCP pancreatitis, the MICHISUJI may be clinically useful, although confirmation in a clinical trial is needed. However, although the loop shape may help prevent duct penetration 10 11 , creation of the loop shape may make guidewire passage through stricture sites more challenging. This function should therefore also be evaluated in an experimental study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several authors have described the clinical benefits of using a loop-tip guidewire during biliary cannulation 10 11 . Compared with conventional guidewires, the risk of insertion into a pancreatic branch duct is lower with a loop-tip guidewire due to its shape.…”
Section: Introductionmentioning
confidence: 99%
“…The major problem associated with pancreatic duct endoscopic intervention is postoperative pancreatitis. GW insertion into the pancreatic duct is considered to be a risk factor for pancreatitis and injury of the pancreatic duct caused by the GW may result in serious outcomes [26, 11]. Although stent placement in the pancreatic duct is reported to be beneficial for prevention of the incidence of PEP caused by duodenal papilledema [710], the preventive effect against PEP in cases with injury of the pancreatic duct has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al have reported on the preventive effect of loop-tipped GWs against PEP [6]. Loop-tipped GWs resulted in less frequent unintended insertion of the guidewire into a side branch of the pancreatic duct than conventional GWs and led to significantly lower serum amylase levels after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation